Exploring fermentation strategies for enhanced lactic acid production with polyvinyl alcohol-immobilized Lactobacillus plantarum 23 using microalgae as feedstock. (July 2020) - Chen, Po-Ting; Hong, Zih-Syuan; Cheng, Chieh-Lun; Ng, I-Son; Lo, Yung-Chung; Nagarajan, Dillirani; Chang, Jo-Shu
Highlights: Lactic acid (LA) fermentation allows green production of lactic acid. PVA-immobilization of L. plantarum enhanced LA titer and yield by 40%. Continuous fermentation with glucose gave the highest productivity of 14.2 g/L/h. In situ lactic acid removal during fermentation improved LA productivity & yield. LA productivity reached 9.93 g/L/h when using microalgal hydrolysate as substrate. Abstract: Lactic acid (LA) fermentation was conducted with suspended and immobilized cells of an isolated Lactobacillus plantarum 23 strain using various fermentation strategies. Glucose and an alternative, relatively inexpensive carbon source - the hydrolysate of microalga Chlorella vulgaris ESP-31, were used as the carbon source. Batch fermentation using immobilized cells of L. plantarum 23 could enhance LA titer and yield by 43% and 39%, respectively, when compared with the suspended culture. Fed-batch culture integrated with in situ LA removal via ion exchange raised LA productivity by 72% by overcoming product inhibition. The highest LA productivity from glucose with PVA immobilized cells was 14.22 g/L/h, achieved under continuous operation at 50% w/v loading of immobilized beads and hydraulic retention time (HRT) of 2 h. PVA immobilized L. plantarum 23 could also use microalgal hydrolysate as the renewable carbon source, and the highest LA productivity was 9.93 g/L/h under continuous fermentation at 4 h HRT.